Crafting a story about an African interpreter on colonial South Africa’s Eastern Frontier: Roger Levine’s narrative of the life of Jan Tzatzoe - Bank, Andrew (Kronos: Southern African Histories, 2017)
A Living Man from Africa will be the first book to be published in a potentially exciting new Yale University Press series entitled 'New Directions in Narrative History'. The series editors are John Demos of Yale and Aaron Sachs of Cornell, both of whom have published prize-winning books that appeal to both popular and academic audiences. Levine employs the opening line from the Preface of Demo's The Unredeemed Captive - 'MOST OF ALL, I wanted to write a story' - as key inspiration for his own narrative choices. 'Most of all, I wanted to his [Jan Tzatzoe's] story Levine asserts. It is a self-reflexive focus on ways story-telling as a way of returning history to its literary roots that is the foremost contribution of Levine's book. The book is also important as an unusually detailed and extended biography of the career of an African translator whom Levine casts as an intellectual.